Icariin protects against iron overload‐induced bone loss via suppressing oxidative stress. Issue 7 (1st November 2018) - Jing, Xingzhi; Du, Ting; Chen, Kun; Guo, Jiachao; Xiang, Wei; Yao, Xudong; Sun, Kai; Ye, Yaping; Guo, Fengjing
Abstract: Iron overload is common in patients with diseases such as hemoglobinopathies, hereditary hemochromatosis or elderly men and postmenopausal women. This disorder is frequently associated with bone loss and recently has been considered as an independent risk factor for osteoporosis. By excess reactive oxygen species (ROS) production through Fenton reaction, iron could induce osteoblast apoptosis, inhibit osteoblast osteogenic differentiation. Moreover, Iron could also promote osteoclasts differentiation and bone absorption. The goal of the study is to investigate whether icariin could reverse iron overload‐induced bone loss in vitro and in vivo. Icariin is the major active ingredient of Herba Epimedii and has antioxidant, antiosteoporosis functions. In the current study, we demonstrated that oral administration of icariin significantly prevented bone loss in iron overloaded mice. Icariin could protect against iron overload‐induced mitochondrial membrane potential dysfunction and ROS production, promote osteoblast survival and reverse the reduction of Runx2, alkaline phosphatase, and osteopontin expression induced by iron overload. Icariin also inhibited osteoclasts differentiation and function. Moreover, we also found that icariin remarkably reduced iron accumulation in bone marrow, suggesting that icariin has the ability to regulate systemic iron metabolism in vivo. These results indicated that icariin could be a potential natural resource for developing medicines to prevent or treat iron overload‐induced osteoporosis. Abstract : Icariin could protect against iron overload‐induced mitochondrial membrane potential dysfunction and reactive oxygen species production, promote osteoblast survival and reverse the reduction of Runx2, alkaline phosphatase, and osteopontin expression induced by iron overload. Icariin also inhibited osteoclasts differentiation and function and iron accumulation in bone marrow.